Maslahah Evaluation of Judges' Sentences for Domestic Violence Crimes at the Majene District Court - Noercholis Rafid. A; Fajri, Muhammad; Noor, Khairun Nizam Mohd. (Universitas Islam Negeri Alauddin Makassar, 2023)
The study aimed to analyze the factors that contributed to the judge's lenient sentence towards a defendant charged with domestic violence at the Majene District Court. Additionally, the study sought to examine the maslahah value inherent in the judge's decision. The study conducted was normative research that involved analyzing the decisions made by judges. Additionally, interviews were conducted with multiple judges to gain insights into their decision-making processes. The study employed a normative syar'i approach to examine judges' decisions by utilizing maslahah analysis from Islamic legal theory. According to the study's findings, the judge's decision was influenced by the maslahah value, which prioritized the restoration of the perpetrator's household. This was due to the perpetrator's expression of regret and the establishment of peace between the involved parties. The statement suggests that there is a comparison between the obligation of maintaining a household and the imposition of prison sentences ranging from 1-10 years on perpetrators who are responsible for victimizing their wives. The imposition of prison sentences can have negative consequences for both the offender and society as a whole, as it impacts their ability to meet basic needs.